Pengolahan Sampah Organik Menggunakan Black Soldier Fly (BSF) di Pasar Ikan Modern Muara Baru, Jakarta Utara - Pramiati Purwaningrum; Ratnaningsih; Petrus Pito Fritz Kleden (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The problem of waste is still the main topic of discussion. One of the sources of waste in the city is the market. The waste produced is in the form of organic waste and inorganic waste that has not yet been processed or recycled. Muara Baru Modern Fish Market is one of the fish markets as the largest fish auction centre in Penjaringan District, North Jakarta. This research aims to determine the amount of waste generated, the composition of the waste, and the protein content produced through several research variations. The research variations were determined based on the composition of organic waste combined with the amount of feed given to Black Soldier Fly (BSF). The volume of waste produced was 1045 kg/day from both wet and dry house sources. The composition of the waste sampled included organic waste consisting of food waste, food losses and fish waste up to 50.45%, while inorganic waste consisting of various types of plastic and paper was up to 49.55%. The potential for recyclable waste is 98.5%. The protein content obtained from the processing of organic waste using BSF in all research variants met the SNI quality requirements, the highest protein content being 31.8% in the 100% food waste research variant.